The Asian law and society reader - Chua, Lynette J. 1977-; Engel, David M.; Liu, Sida 1980- (Cambridge University Press, 2023)
The first reader on Asian law and society scholarship, this book features reading selections from a wide range of Asian countries - East, South, Southeast and Central Asia - along with original commentaries by the three editors on the theoretical debates and research methods pertinent to the discipline. Organized by themes and topical areas, the reader enables scholars and students to break out of country-specific silos to make theoretical connections across national borders. It meets a growing demand for law and society materials in institutions and universities in Asia and around the world. It is written at a level accessible to advanced undergraduate students and graduate students as well as experienced researchers, and serves as a valuable teaching tool for courses focused on Asian law and society in law schools, area studies, history, religion, and social science fields such as sociology, anthropology, politics, government, and criminal justice